The Effectiveness of Aceh's Jinayat Qanun on Crime Rates in the Community in a Review of Legal Socialization - Muzakkir (Al-Manahij: Jurnal Kajian Hukum Islam, 2022)
Qanun Jinayat Aceh reflects Aceh's condition after being recognized as an area that is allowed to implement Islamic law. Even though it is legal, the next problem is how to actualize it so that it is not only a juridical struggle. The challenge in implementing the qanun jinayat by the Aceh government is how to be objective, not sharp down and blunt up. The next challenge is how the community is aware of the law with various legal socializations carried out by the Aceh Islamic Shari'a Service. This research is classified as field research with a qualitative approach. The methodology used is a juridical-empirical study. This means how the law's legality is associated with events and phenomena in the field. The primary sources in this study were informants at the Syariat Islam service in Aceh Tamiang and Langsa City, lecturers in the field of Islamic Criminal Law (HPI) at IAIN Langsa, MPU Aceh Tamiang and MPU Langsa City, and communities around Aceh Tamiang and Langsa cities. The results of the study conclude that the Qanun Jinayat has not been effective in suppressing the crime rate in Aceh. The causes are, first, because legal socialization is not right on target and only touches some levels of society. Second, many people still choose to settle jinayat cases through customary law with light sanctions, which does not have a deterrent effect.